The prospective relationship between social cohesion and depressive symptoms among older adults from Central and Eastern Europe - Bertossi Urzua, Carla; Ruiz, Milagros A; Pajak, Andrzej; Kozela, Magdalena; Kubinova, Ruzena; Malyutina, Sofia; Peasey, Anne; Pikhart, Hynek; Marmot, Michael; Bobak, Martin (Journal of epidemiology and community health, 2019)
BACKGROUND: Social cohesion has a potential protective effect against depression, but evidence for Central and Eastern Europe is lacking. We investigated the prospective association between social cohesion and elevated depressive symptoms in the Czech Republic, Russia and Poland, and assessed whether alcohol drinking and smoking mediated this association. METHODS: Cohort data from 15 438 older urban participants from the Health, Alcohol and Psychosocial factors In Eastern Europe project were analysed. Baseline social cohesion was measured by five questions, and depressive symptoms were measured 3 years later by the 10-item Center for Epidemiological Depression (CES-D) Scale. Nested logistic regression models estimated ORs of elevated depressive symptoms (CES-D 10 score ≥4) by z-scores and tertiles of social cohesion. RESULTS: Per 1 SD decrease in social cohesion score, adjusted ORs of elevated depressive symptoms were 1.13 (95% CI 1.05 to 1.23) and 1.05 (95% CI 0.99 to 1.13) in men and women, respectively. Further adjustment for smoking and drinking did not attenuate these associations in either men (OR=1.13, 95% CI 1.05 to 1.22) or women (OR=1.05, 95% CI 0.99 to 1.13). Similarly, the fully adjusted ORs comparing the lowest versus highest social cohesion tertile were 1.33 (95% CI 1.10 to 1.62) in men and 1.18 (95% CI 1.01 to 1.39) in women. CONCLUSIONS: Lower levels of social cohesion was associated with heightened depressive symptoms after a 3-year follow-up among older Czech, Russian and Polish adults. These effects appeared stronger in men, and alcohol and smoking played no appreciable role in this association.
Keywords: senioři; charakteristiky bydlení; Poland; Residence Characteristics; Russia; deprese; depression; Socioeconomic Factors; Česká republika; Cohort Studies; interpersonální vztahy; Depression; Rusko; Interpersonal Relations; social cohesion; mužské pohlaví; Czech Republic; Polsko; kohortové studie; socioekonomické faktory; cohort study; městské obyvatelstvo; ženské pohlaví; Humans; depressive symptoms; Central and Eastern Europe; Attitude to Health; rizikové faktory; postoj ke zdraví; pití alkoholu; Alcohol Drinking; Urban Population; Female; Aged; Risk Factors; lidé; Male; social capital